Museum Cultural and Creative Brand System Based on Public Cultural Platform Construction (Journal of Global Arts Studies, 2025)
Background： Museums are vital for preserving civilization and providing cultural services. However, homogenization, confused positioning, and lack of systematicity in state-owned museum cultural and creative product development are significant concerns in the cultural sector. Objective： This study systematically analyzes state-owned museum cultural and creative branding's essential attributes and system construction, then proposes strategies and pathways for building their C&C brand system. This aims to enrich the theoretical framework for such development. Methods: Integrating public cultural services, museology, and brand management theories, this research defines the core logic for state-owned museum brand and C&C development, where cultural undertakings lead cultural industries. It identifies existing problems through a systematic analysis of case studies and practical experiences. Results: The study defines "cultural undertakings guiding cultural industries" as the core logic for state-owned museums and constructs a cultural and creative brand system framework based on public cultural platforms. The framework includes a five-dimensional path of brand value definition, market analysis, product innovation, marketing, and evaluation; establishes an industry-university-research mechanism of "museum-led, social participation, diversified development, and platform-based sales"; and forms a hierarchical brand system, where national museums inherit cultural context, provincial museums showcase diversity, and municipal museums create regional characteristics. Conclusion: Introducing a public cultural service-based system, this study creates a cultural undertaking-led industry paradigm for cultural and creative brands. This innovation addresses homogenization and attribute confusion in state-owned museum cultural and creative development, revitalizing the cultural industry. Through government guidance, museum platform operations, and social collaboration, it secures cultural dissemination and economic benefits, cultivating a distinct Chinese cultural and creative development model and discourse.
Keywords: Public Cultural Services; State-Owned Museums; Museum Cultural and Creative Products; Brand System